Chinese heritage in the making : experiences, negotiations and contestations - Maags, Christina; Svensson, Marina, 1961- (IIAS publications series. Monographs., 2018)
The language of cultural heritage is pervasive in China today. In official rhetoric and policy it is linked to political and economic goals, and serves as a resource for political legitimacy, soft power, and economic development. But the heritage discourse has also opened up space for and legitimized many cultural practices as well as encouraged new actors to appropriate the new discourse to protect their own traditions. Individual citizens, local communities, and heritage experts, are thus today debating, performing and consuming a diverse cultural heritage. The book pays particular attention to individual citizens, local communities, religious associations, and heritage experts and focuses on their possibilities for voice and agency, how the heritage-isation process affects different groups of people, as well as the interplay between top-down and bottom-up processes in the heritage field.